Endovascular Management of Nonvariceal Upper Gastrointestinal Bleeding - Partovi, Sasan; Vij, Arjun; Kapoor, Baljendra; McLennan, Gordon (Digestive Disease Interventions, 2018)
Nonvariceal upper gastrointestinal bleeding (UGIB) is associated with significant morbidity and mortality among hospitalized patients and thus presents a treatment challenge for the interventional radiologist. Common causes of nonvariceal UGIB include peptic ulcer disease, Mallory–Weiss tear, erosive inflammatory changes, ulcer disease, malignancy, and vascular malformations. Noninvasive imaging workup for this condition may include computed tomography angiography and tagged red blood cell scan. Invasive angiography allows for both the diagnosis and endovascular treatment of nonvariceal UGIB. Transcatheter embolization can be performed using a variety of embolic agents, such as coils, vascular plugs, and Gelfoam. For patients with negative angiography results despite the presence of clinically and endoscopically significant UGIB from a known source such as gastric ulcer or duodenal ulcer, the left gastric or gastroduodenal artery can be empirically embolized. In high-risk patients with multiple comorbidities who have failed endoscopic therapy, endovascular embolization is associated with lower complication rates compared with open surgery. In this review, we discuss current management strategy and endovascular techniques for the management of the nonvariceal upper GI hemorrhage.
Keywords: upper gastrointestinal bleeding; transcatheter embolization; prophylactic embolization